Evaluation the frequency of the IGF2 ApaI polymorphism in Iranian elite judo athletes - mohsen alinaghizadeh; reza Gharakhanlou; Mahdieh Molanouri shamsi (Shahid Beheshti University, 2020)
Purpose: Finding genetic structures effecting on athletic performance is an important step in developing methods related to talent identification and as well as personalizing athletic training programs. The previous investigations revealed the insulin-like growth factor (IGF2) is associated with body mass index, fat-free mass, hand grip strength and leg strength. The purpose of this study was to evaluate the frequency of IGF2 rs680 polymorphism in Iranian male judo athletes. Methods: The athlete group includes 40 elite judo athletes who had medals in Asian and World championship. The control group comprised of 120 health non-athletes men. DNA was extracted from the peripheral blood using a non-enzymatic method and genotyping was conducted by PCR method for identifying the IGF2 rs680 polymorphism. The distribution frequency of this polymorphism was determined by chi-square analysis. Results: There were no significant differences in genotype frequency between judo athletes (G/G=37.5%, G/A=42.5%, A/A=20%) and control group (G/G=30.8%, G/A=48.3%, A/A=20.8%) (in all genotypes P>0.5) and also in allele frequency between judo athletes (G=58.8%, A=41.2%) and control group (G=55%, A=45%)(P=0.55). Conclusion: Regarding that the exercise is polygenic and many genes play a role, and given that judo sport is affected by various factors and is not completely dependent on a factor such as strength or endurance, it is likely that the polymorphism IGF2 rs680 is not a significant genetic marker in judo sport in the Iranian male population.